2-SeCD treatment extends lifespan, improves healthspan and enhances resistance to stress in Caenorhabditis elegans. Issue 76 (13th October 2017) - Zhou, Lin; Fu, Xueqi; Luo, Yi; Du, Fangzhou; Wang, Hua; Xing, Shu; Li, Wannan; Ma, Junfeng
Abstract : Aging is primarily caused by reactive oxygen species (ROS). Abstract : Aging is primarily caused by reactive oxygen species (ROS). 2-Selenium-bridged β-cyclodextrin (2-SeCD) is an enzyme with glutathione peroxidase (GPX)-like activity, which indicates that it might be an important ROS scavenger in vivo . However, its effects on aging are unknown. In this study, we studied the dose-dependent effects of 2-SeCD on the lifespan, healthspan and resistance to stress of Caenorhabditis elegans . The mean lifespan of nematodes treated with 0.05, 0.5, and 5 mM 2-SeCD increased significantly in a dose-dependent manner. Healthspan also improved, as revealed by increased motility and GPX activity and decreased lipid peroxidation and ROS level, indicating that DNA damage was curbed. In addition, nematodes treated with 2-SeCD were more resistant to heat stress, UV irradiation and H2 O2 -induced oxidative stress. Our findings indicate that 2-SeCD extends the lifespan of C. elegans, improves the healthspan and enhances the resistance to stress.